2020
DOI: 10.1002/chem.202001249
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Adsorption Selectivity of ZIF‐8 by Amorphization

Abstract: Figure 3. a) Photograph and b) SEM imageo fthe self-standing a m ZIF-8 membrane. c) Single gas permeability and d) the corresponding ideal selectivities of a m ZIF-8membrane measured by time-lagpermeationt echnique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 31 publications
(24 reference statements)
0
34
0
Order By: Relevance
“…Also, experimental validation is encouraged, though in our results, the enhancement in porosity was observed for the low level of amorphization. Nevertheless, the degree of amorphization can be tuned by controlling the time of ball-milling , or by adjusting the compression pressure …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, experimental validation is encouraged, though in our results, the enhancement in porosity was observed for the low level of amorphization. Nevertheless, the degree of amorphization can be tuned by controlling the time of ball-milling , or by adjusting the compression pressure …”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al 5 produced a zeolitic imidazolate framework (ZIF) glass with permanent porosity, but it still displayed a smaller surface area compared to the pristine crystalline structure. Also, a recent experimental study by Ma et al 6 showed that the mechanically amorphized ZIF-8 has less capacity for gas uptake than the parent structure; however, the amorphous structure displayed huge improvement in terms of selectivity. Purewal et al 7 revealed that the amorphized MOF-5 exhibits higher volumetric uptake for hydrogen than the parent structure.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Recently, mechanical amorphisation of ZIF-8 [Zn(mIm) 2 ; mIm -2-methylimidazolate], to form a m ZIF-8 (a m denoting amorphisation by ball milling), was found to enhance the adsorption selectivity of C 3 H 6 over C 3 H 8 . 26,27 Despite this, investigations into disordered MOFs for applications in gas storage and separation are of comparatively low prevalence with respect to their crystalline counterparts, particularly in the area of C 3 H 6 /C 3 H 8 separation.…”
Section: Introductionmentioning
confidence: 99%
“…25 Recently, mechanical amorphisation of ZIF-8 [Zn(mIm)2; mIm -2-methylimidazolate], to form amZIF-8 (am denoting amorphisation by ball milling), was found to enhance the adsorption selectivity of C3H6 over C3H8. 26,27 Despite this, investigations into disordered MOFs for applications in gas storage and separation are of comparatively low prevalence with respect to their crystalline counterparts, particularly in the area of C3H6/C3H8 separation.…”
Section: Introductionmentioning
confidence: 99%